Design, Synthesis, and Biological Assessment of Bis-thiazole Derivatives as Promising Anticancer Agents with Molecular Docking Insights - Abolibda, Tariq Z.; Zaki, Magdi E.A.; Boraie, Waleed E.; Farag, Basant; Gomha, Sobhi M. (Current Organic Synthesis, 2025)
IntroductionThiazoles and bis-thiazoles are recognized for their anticancer and antitubercular properties, making them crucial in medicinal chemistry. This study focuses on synthesizing and evaluating novel bis-thiazole derivatives.Materials and MethodsBis-thiosemicarbazone derivative 3 was used as a precursor to synthesize bis-thiazole (6a-f, 12a-h) and bis-thiazolone (9a-d) derivatives through reactions with appropriate reagents. Anticancer activity was screened using the MTT assay on HCT-116 cells, while antitubercular activity was tested using the microplate Alamar blue assay (MABA). The derivatives were synthesized under optimized reflux conditions and characterized using spectroscopic techniques. Biological assays evaluated their therapeutic potential.ResultsThe compounds displayed variable cytotoxicity and antitubercular efficacy. Molecular docking studies on dihydrofolate reductase (DHFR) revealed significant interactions, suggesting potential mechanisms of action.DiscussionThe results highlight the influence of structural features on biological activity, with active compounds showing favorable interactions and docking scores.ConclusionBis-thiazole and bis-thiazolone derivatives exhibit promising anticancer and antitubercular potential, warranting further investigation for therapeutic applications.
Keywords: anticancer